Zur Verleihung der Ehrensenatorwürde der Universität Hamburg an Professor Wolfgang K. H. Panofsky am 6. Juli 2006 - Spitzer, Hartwig (Hamburger Universitätsreden Neue Folge, 2007)
On July 6, 2006, Professor Wolfgang K. H. Panofsky from Stanford (USA) was awarded the honorary senator status of the University of Hamburg in a special session of the Academic Senate. The speeches given are documented in this volume. The volume is supplemented by an interview given by Professor Panofsky on July 6, 2006 in Hamburg, and a tabular overview of his career, his public functions and honours.Wolfgang K. H. Panofsky, born in Berlin in 1919, spent most of his childhood and adolescence in Hamburg. Forced to emigrate by the Nazis, he came to the USA in 1934. After studying physics in Princeton and at the California Institute of Technology, he quickly gained a great reputation in elementary particle physics research. He was one of the initiators of the construction of a large electron linear accelerator, which began operation at the Stanford Linear Accelerator Center (SLAC) in 1972. From 1961 until his retirement in 1984, Professor Panofsky was director of this institute.Through his great professional authority, his personal integrity and his commitment to peace and humanism, he became a role model for many young scientists. His role model was one of the formative influences that contributed to the founding of the Carl Friedrich von Weizsäcker Center for Science and Peace Research at the University of Hamburg.